Compartmentalization of TNF and IL-6 in meningitis and septic shock - Anders Waage; Alfred Halstensen; Terje Espevik; Petter Brandtzæg (Mediators of Inflammation)
We examined the compartmentalization of bioactive tumour necrosis factor (TNF) and interleukin 6 (IL-6) to the subarachnoid space and systemic circulation in patients with meningococcal meningitis and septic shock/bacteraemia. In patients with meningitis, median levels of TNF in 31 paired samples of cerebrospinal fluid (CSF) and serum were respectively 783 pg/ml and below detection limit (p < 0.001) and median levels of IL-6 were 150 ng/ml and 0.3 ng/ml (p < 0.0001). In patients with septic shock without meningitis, median levels in paired samples of CSF and serum were respectively below detection limit and 65 pg/ml (not significant, (ns)) (TNF, eleven patients) and 1.3 ng/ml–3 ng/ml (ns) (IL-6, nine patients). The data show that TNF and IL-6 are localized to the subarachnoid space in patients with meningitis although the blood–brain barrier is penetrable to serum proteins. On the other hand, patients with septic shock tend to have cytokines in both serum and CSF.